Literature Review: Policy Analysis on Exclusive Breastfeeding for Working Mothers: Tinjauan Pustaka: Analisis Kebijakan Pemberian ASI Eksklusif bagi Ibu Bekerja - Husnul Khotimah; Dumilah Ayuningtyas (Prodi DIII Kebidanan La Tansa Mashiro, 2024)
Exclusive breastfeeding is an important part of fulfilling infant nutrition to achieve optimal growth and development in early life and subsequent growth. Some mothers cannot provide exclusive breastfeeding, especially working mothers. The purpose of this study was to analyze health policies on providing exclusive breastfeeding to working mothers. This study is a systematic review conducted in 2024 which was taken from the search site